Inorganic floor coating and preparation method thereof
By covering the method of mixing hydroxyxylite and silicon solidaries and water thermal method to prepare composite fillers, the problem of poor waterproofing and poor storage resistance of silicon -soluble floor coatings and poor storage resistance is solved. Inorganic floor coatings.
Patent Information
- Application Number
- CN202411919534.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-01-24
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing silicon sol floor coatings have problems such as poor waterproofness, flowering after drying, cracking, and poor storage resistance.
The hybrid silicon solids that are mixed with hydroxyl -based limestone and silicon -soluble, and composite fillers are prepared through the water thermal method, combined with hydrophobic treatment of ethylene triameter silicane, forming an efficient inorganic floor coatings.
It improves the waterproof, leveling, abrasion resistance, anti -static and storage resistance of the inorganic floor coatings, avoiding the problems of flowering and cracking after drying, and shortening the drying time.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of floor coatings, and in particular to an inorganic floor coating and a preparation method thereof. Background Art
[0002] Floor coatings can protect the ground and play a role in dust prevention, wear resistance, cleaning, and moisture resistance, so they are widely used and promoted in commercial floors, modern industrial floors, garage floors, etc. According to the chemical composition of the film-forming materials, floor coatings are mainly divided into organic floor coatings and inorganic floor coatings. Among them, the film-forming materials of organic floor coatings are organic materials, mainly including epoxy floor coatings, polyurethane floor coatings, acrylic floor coatings, etc., and the film-forming materials of inorganic floor coatings are inorganic materials, mainly including silicate floor coatings, phosphate floor coatings, silica sol floor coatings, etc. Organic floor coatings have good waterproofness, wear resistance, acid and alkali resistance, but poor high temperature resistance, low temperature resistance, and fire resistance, and are easy to volatilize a large amount of toxic substances, which have an impact on the environment and human health. Therefore, more and more users are beginning to use inorganic floor coatings.
[0003] Inorganic floor coatings have good UV resistance, high temperature resistance, low temperature resistance, fire resistance, antistatic properties, strong adhesion, and no volatile toxic substances. The most commonly used inorganic floor coating is silica sol floor coating. The silica particles in silica sol floor coating can cross-link with each other during the curing process of the coating, thereby improving the hardness and wear resistance of the floor coating. In addition, the cross-linked silica particles also have the advantages of acid and alkali resistance, high temperature resistance, low temperature resistance, good fire resistance, and strong adhesion to the ground. However, silica sol floor coatings have the following disadvantages: First, the surface of the cross-linked silica particles contains hydrogen bonds, which can form a hydrate film, thereby playing a waterproof role, but the waterproof effect is limited, resulting in poor waterproofness of the existing silica sol floor coating; second, the silica particles in the silica sol floor coating have a large volume shrinkage during cross-linking, resulting in the silica sol floor coating having the problem of floweriness and cracking after drying; third, silica sol is easy to agglomerate, resulting in poor storage resistance of silica sol floor coating.
[0004] In order to solve the above problems, the most commonly used method is to add organic fillers with layered structures or silane coupling agents with hydrophobic functional groups to organic floor coatings. The commonly used organic fillers with layered structures are organic montmorillonite. When the silica particles in the silica sol floor coating are cross-linked with each other, they can intercalate the organic montmorillonite. The organic montmorillonite has good dispersibility and hydrophobicity, which can improve the waterproofness of the silica sol floor coating and will not affect the cross-linking between the silica particles. However, the organic montmorillonite is flaky, which will affect the leveling of the silica sol floor coating, and will also affect the cross-linking speed of the silica particles, further affecting the drying time of the silica sol floor coating; silane coupling agents with hydrophobic functional groups After hydrolysis, the silane alkoxy groups in the agent can form covalent bonds with the hydrogen bonds in the silica particles. The hydrophobic functional groups can improve the waterproofness of the silica sol floor coating. However, the silane coupling agent cannot solve the problem of large volume shrinkage of silica particles during cross-linking. Moreover, since the silica sol is cross-linked through hydroxyl groups during cross-linking, the number of hydroxyl groups is reduced after the silane coupling agent reacts with the hydroxyl groups, which will also affect the cross-linking density of the silica particles, further affecting the hardness, wear resistance, high temperature resistance, low temperature resistance, antistatic properties and adhesion to the ground of the silica sol floor coating. Summary of the invention
[0005] In view of the shortcomings of the prior art, the present invention provides an inorganic floor coating and a preparation method thereof. The prepared inorganic floor coating has good waterproofness, leveling, wear resistance, high temperature resistance, low temperature resistance, antistatic property, and storage resistance, high hardness, no problems of blooming and cracking after drying, short drying time, and strong adhesion to the ground.
[0006] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows: An inorganic floor coating, comprising the following components by weight: 65-70 parts of mixed silica sol, 13-15 parts of composite filler, 7.5-8 parts of pigment, 3.5-4 parts of lithium carbonate, 1-1.2 parts of acrylic acid, and 0.5-0.6 parts of tributyl phosphate; The pigment is one of iron oxide or chromium oxide; The preparation method of the mixed silica sol comprises the following steps: coating and mixing; The coating comprises adding hydroxyapatite and polyvinyl alcohol aqueous solution into a reaction kettle and stirring, controlling the stirring temperature to be room temperature, the stirring speed to be 200-300rpm, stirring for 1-1.5h, adding into a centrifuge and centrifuging, controlling the centrifugal temperature to be room temperature, the centrifugal speed to be 9000-10000rpm, centrifuging for 20-25min, taking a precipitate, washing it with deionized water and drying it, adding it into a reaction kettle with deionized water and stirring, controlling the stirring temperature to be 40-60°C, the stirring speed to be 200-300rpm, stirring for 10-20min, dropping glutaraldehyde aqueous solution, continuing stirring for 2.5-3h after the dropping is completed, adding into a centrifuge and centrifuging, controlling the centrifugal temperature to be room temperature, the centrifugal speed to be 9000-10000rpm, centrifuging for 20-25min, taking a precipitate, washing it with deionized water and drying it, and obtaining coated hydroxyapatite; In the coating, the dosage ratio of hydroxyapatite, polyvinyl alcohol aqueous solution, deionized water, and glutaraldehyde aqueous solution is 100g:950-1000mL:900-1000mL:350-400mL; The particle size of the hydroxyapatite is 200 nm; The polyvinyl alcohol aqueous solution is polyvinyl alcohol 1788 aqueous solution with a mass concentration of 1%; The mass concentration of the glutaraldehyde aqueous solution is 5%; The dropping speed of the glutaraldehyde aqueous solution is 10-15 mL / min; The mixing is performed by adding the silica sol and the coated hydroxyapatite into a reaction kettle and stirring, the temperature during stirring is controlled to be room temperature, the stirring speed is 200-300 rpm, and the stirring is performed for 50-60 minutes to obtain a mixed silica sol; In the mixing, the ratio of silica sol to coated hydroxyapatite is 5000mL:14-15g; The pH of the silica sol is 9.5, the particle size is 15 nm, and the mass content of silicon dioxide is 30%; The preparation method of the composite filler comprises the following steps: compounding and hydrophobizing; The composite comprises mixing boron nitride and deionized water, performing ultrasonic oscillation, and then adding the mixture into a reactor for stirring, controlling the stirring temperature to be room temperature, the stirring speed to be 200-300 rpm, stirring for 10-20 min, dripping titanium tetrachloride aqueous solution, dripping aluminum chloride aqueous solution after the dripping, dripping sodium hydroxide aqueous solution after the dripping, continuing to stir for 50-60 min after the dripping, adding the mixture into a hydrothermal reactor, sealing the hydrothermal reactor and adding the mixture into an oven for hydrothermal reaction, controlling the temperature during the hydrothermal reaction to be 170-180° C., performing the hydrothermal reaction for 8-9 h, taking out and opening the hydrothermal reactor, adding the mixture into a centrifuge for centrifugation, controlling the temperature during the centrifugation to be room temperature, the centrifugal speed to be 9000-10000 rpm, centrifuging for 20-25 min, taking the precipitate, washing it with deionized water and drying it to obtain a primary composite filler; In the composite, the amount ratio of boron nitride, deionized water, titanium tetrachloride aqueous solution, aluminum chloride aqueous solution, and sodium hydroxide aqueous solution is 200g:2000-2500mL:60-65mL:135-145mL:30-34mL; The boron nitride is spherical nano boron nitride with a particle size of 200nm; The mass concentration of the titanium tetrachloride aqueous solution is 30%; The mass concentration of the aluminum chloride aqueous solution is 10%; The mass concentration of the sodium hydroxide aqueous solution is 10%; The dropping speed of the titanium tetrachloride aqueous solution is 4-5 mL / min; The dropping speed of the aluminum chloride aqueous solution is 8-10 mL / min; The dropping speed of the sodium hydroxide aqueous solution is 4-5 mL / min; The temperature of the ultrasonic oscillation is room temperature, the frequency is 25-30kHz, and the time is 30-40min; The hydrophobic treatment comprises adding the primary composite filler, vinyl trimethoxysilane and anhydrous ethanol to a reaction kettle with a reflux device, stirring and refluxing, controlling the temperature during stirring and reflux to be 45-55° C., the stirring speed to be 200-300 rpm, stirring and refluxing for 6-7 hours, adding the primary composite filler to a centrifuge for centrifugation, controlling the temperature during centrifugation to be room temperature, the centrifugal speed to be 9000-10000 rpm, centrifuging for 20-25 minutes, taking the precipitate, washing it with anhydrous ethanol and drying it to obtain a composite filler; In the hydrophobization, the usage ratio of the primary composite filler, vinyltrimethoxysilane and anhydrous ethanol is 200g:20-25mL:3000-3200mL; A preparation method of an inorganic floor coating comprises the following steps: weighing raw materials according to a specified weight ratio, adding a mixed silica sol into a high-speed disperser for high-speed dispersion, controlling the temperature during high-speed dispersion to room temperature, controlling the rotation speed to 5000-5500 rpm, dispersing at high speed for 10-20 minutes, adding a composite filler, dispersing at high speed for 40-50 minutes, adding a pigment, lithium carbonate, acrylic acid, and tributyl phosphate, stopping stirring and standing for 30-40 minutes, continuing high-speed dispersion, controlling the temperature during high-speed dispersion to room temperature, controlling the rotation speed to 2700-3000 rpm, dispersing at high speed for 1.5-2 hours, and obtaining the inorganic floor coating.
[0007] Compared with the prior art, the present invention has the following beneficial effects: (1) The inorganic floor coating prepared by the present invention does not have the problem of blooming or cracking after drying. The appearance before drying is a uniform liquid, and the appearance after drying is a flat surface without blooming or cracking; (2) The inorganic floor coating prepared by the present invention has good environmental protection, and the volatile organic compound content (VOC) is 0g / L; (3) The inorganic floor coating prepared by the present invention has good leveling properties, and the initial fluidity is 151-160mm; (4) The inorganic floor coating prepared by the present invention has good wear resistance, and the wear resistance (750g / 500r) is 0.011-0.015g; (5) The inorganic floor coating prepared by the present invention has good antistatic properties and a surface resistance of 1.0×10 9 -2.3×10 9 Ω; (6) The inorganic floor coating prepared by the present invention has high hardness, with a pencil hardness of 6H; (7) The inorganic floor coating prepared by the present invention has a short drying time, with a surface drying time of 2 hours and a practical drying time of 30-31 hours; (8) The inorganic floor coating prepared by the present invention has strong adhesion to the ground, and the adhesion grade is level 1; (9) The inorganic floor coating prepared by the present invention has good waterproofness, water resistance (168h) is no blistering, no peeling, and the water contact angle is 100-104°; (10) The inorganic floor coating prepared by the present invention has good storage resistance. After the inorganic floor coating prepared by the present invention is sealed and stored at 25°C for 3 months, the appearance before drying is a uniform liquid; (11) The inorganic floor coating prepared by the present invention has good high temperature resistance. After the inorganic floor coating prepared by the present invention is left to stand at 60°C for 28 days, the wear resistance (750g / 500r) is 0.011-0.017g, and the tensile bonding strength is 3.0-3.6MPa; (12) The inorganic floor coating prepared by the present invention has good low temperature resistance. After the inorganic floor coating prepared by the present invention is left to stand at -40°C for 28 days, the wear resistance (750g / 500r) is 0.012-0.017g, and the tensile bonding strength is 3.1-3.5MPa. DETAILED DESCRIPTION
[0008] In order to have a clearer understanding of the technical features, purposes and effects of the present invention, the specific implementation methods of the present invention are now described.
[0009] Example 1 An inorganic floor coating, composed of the following components by weight: 65 parts of mixed silica sol, 13 parts of composite filler, 7.5 parts of pigment, 3.5 parts of lithium carbonate, 1 part of acrylic acid, and 0.5 part of tributyl phosphate; The pigment is iron oxide; The preparation method of the mixed silica sol is: 1. Coating: 100g hydroxyapatite and 950mL polyvinyl alcohol aqueous solution were added to a reactor and stirred, the temperature during stirring was controlled to be room temperature, the stirring speed was 200rpm, and the stirring was performed for 1h. The mixture was added to a centrifuge and centrifuged, the temperature during centrifugation was controlled to be room temperature, the centrifugal speed was 9000rpm, and the centrifugation was performed for 20min. The precipitate was washed with deionized water and dried, and 900mL deionized water was added to a reactor and stirred, the temperature during stirring was controlled to be 40°C, the stirring speed was 200rpm, and the stirring was performed for 10min. 350mL glutaraldehyde aqueous solution was added dropwise, the dropping speed was controlled to be 10mL / min, and the stirring was continued for 2.5h after the addition was completed. The mixture was added to a centrifuge and centrifuged, the temperature during centrifugation was controlled to be room temperature, the centrifugal speed was 9000rpm, and the centrifugation was performed for 20min. The precipitate was washed with deionized water and dried to obtain coated hydroxyapatite; The particle size of the hydroxyapatite is 200 nm; The polyvinyl alcohol aqueous solution is polyvinyl alcohol 1788 aqueous solution with a mass concentration of 1%; The mass concentration of the glutaraldehyde aqueous solution is 5%; 2. Mixing: Add 5000 mL of silica sol and 14 g of coated hydroxyapatite into a reactor and stir. Control the stirring temperature to be room temperature and the stirring speed to be 200 rpm. Stir for 50 min to obtain a mixed silica sol. The pH of the silica sol is 9.5, the particle size is 15 nm, and the mass content of silicon dioxide is 30%; The preparation method of the composite filler is: 1. Compounding: After mixing 200g of boron nitride and 2000mL of deionized water, add them to an ultrasonic oscillator for ultrasonic oscillation, control the temperature during ultrasonic oscillation to be room temperature, the frequency to be 25kHz, and the ultrasonic oscillation to be 30min. Add them to a reactor for stirring, control the temperature during stirring to be room temperature, the stirring speed to be 200rpm, and stir for 10min. Add 60mL of titanium tetrachloride aqueous solution, control the dropping speed to be 4mL / min, and after the addition is completed, add 135mL of aluminum chloride aqueous solution, control the dropping speed to be 8mL / min, and after the addition is completed, add 30mL of sodium hydroxide aqueous solution, control the dropping speed to be 4mL / min, and continue to stir for 50min after the addition is completed. Add them to a hydrothermal reactor, seal the hydrothermal reactor, and add them to an oven for hydrothermal reaction, control the temperature during the hydrothermal reaction to be 170℃, and the hydrothermal reaction is 8h. Take out and open the hydrothermal reactor, add them to a centrifuge for centrifugation, control the temperature during centrifugation to be room temperature, and the centrifugal speed to be 9000rpm. Centrifuge for 20min, take the precipitate, wash it with deionized water and dry it to obtain a primary composite filler; The boron nitride is spherical nano boron nitride with a particle size of 200nm; The mass concentration of the titanium tetrachloride aqueous solution is 30%; The mass concentration of the aluminum chloride aqueous solution is 10%; The mass concentration of the sodium hydroxide aqueous solution is 10%; 2. Hydrophobicization: Add 200 g of primary composite filler, 20 mL of vinyltrimethoxysilane, and 3000 mL of anhydrous ethanol to a reactor with a reflux device, stir and reflux, control the temperature during stirring and reflux to 45 ° C, the stirring speed to 200 rpm, stir and reflux for 6 hours, add to a centrifuge for centrifugation, control the temperature during centrifugation to room temperature, the centrifugal speed to 9000 rpm, centrifuge for 20 minutes, take the precipitate, wash it with anhydrous ethanol and dry it to obtain a composite filler.
[0010] A preparation method of an inorganic floor coating, specifically comprising: weighing raw materials according to specified weight parts, adding a mixed silica sol into a high-speed disperser for high-speed dispersion, controlling the temperature during high-speed dispersion to room temperature, controlling the rotation speed to 5000 rpm, dispersing at high speed for 10 minutes, adding a composite filler, dispersing at high speed for 40 minutes, adding pigment, lithium carbonate, acrylic acid, and tributyl phosphate, stopping stirring and standing for 30 minutes, continuing high-speed dispersion, controlling the temperature during high-speed dispersion to room temperature, controlling the rotation speed to 2700 rpm, dispersing at high speed for 1.5 hours, and obtaining the inorganic floor coating.
[0011] Example 2 An inorganic floor coating, comprising the following components by weight: 65-70 parts of mixed silica sol, 13-15 parts of composite filler, 7.7 parts of pigment, 3.5-4 parts of lithium carbonate, 1-1.2 parts of acrylic acid, and 0.5-0.6 parts of tributyl phosphate; The pigment is iron oxide; The preparation method of the mixed silica sol is: 1. Coating: 100g hydroxyapatite and 980mL polyvinyl alcohol aqueous solution were added to a reactor and stirred. The stirring temperature was controlled to be room temperature and the stirring speed was 250rpm. The stirring was performed for 1.5h. The mixture was added to a centrifuge and centrifuged. The temperature during centrifugation was controlled to be room temperature and the centrifugal speed was 9500rpm. The mixture was centrifuged for 22min. The precipitate was washed with deionized water and dried. The mixture was added to a reactor with 950mL deionized water and stirred. The temperature during stirring was controlled to be 50°C and the stirring speed was 250rpm. The mixture was stirred for 15min. 380mL glutaraldehyde aqueous solution was added dropwise. The dropping speed was controlled to be 12mL / min. After the addition was completed, the mixture was stirred for 2.5h. The mixture was added to a centrifuge and centrifuged. The temperature during centrifugation was controlled to be room temperature and the centrifugal speed was 9500rpm. The mixture was centrifuged for 22min. The precipitate was washed with deionized water and dried. The coated hydroxyapatite was obtained. The particle size of the hydroxyapatite is 200 nm; The polyvinyl alcohol aqueous solution is polyvinyl alcohol 1788 aqueous solution with a mass concentration of 1%; The mass concentration of the glutaraldehyde aqueous solution is 5%; 2. Mixing: Add 5000 mL of silica sol and 14.5 g of coated hydroxyapatite into a reactor and stir. Control the stirring temperature to be room temperature and the stirring speed to be 250 rpm. Stir for 55 min to obtain a mixed silica sol. The pH of the silica sol is 9.5, the particle size is 15 nm, and the mass content of silicon dioxide is 30%; The preparation method of the composite filler is: 1. Compounding: After mixing 200g of boron nitride and 2300mL of deionized water, add them to an ultrasonic oscillator for ultrasonic oscillation, control the temperature during ultrasonic oscillation to be room temperature, the frequency to be 25kHz, and the ultrasonic oscillation to be 35min, add them to a reactor for stirring, control the temperature during stirring to be room temperature, the stirring speed to be 250rpm, stir for 15min, add 62mL of titanium tetrachloride aqueous solution, control the dropping speed to be 5mL / min, and after the dropping is completed, add 140mL of aluminum chloride aqueous solution, control the dropping speed to be 9mL / min, After the addition is completed, 32 mL of sodium hydroxide aqueous solution is added dropwise, and the dropping speed is controlled to be 5 mL / min. After the addition is completed, stirring is continued for 55 min, and the mixture is added to a hydrothermal reactor. The hydrothermal reactor is sealed and then added to an oven for hydrothermal reaction. The temperature during the hydrothermal reaction is controlled to be 175°C. The hydrothermal reaction is carried out for 8.5 h. The hydrothermal reactor is taken out and opened, and the mixture is added to a centrifuge for centrifugation. The temperature during the centrifugation is controlled to be room temperature, and the centrifugal speed is 9500 rpm. The mixture is centrifuged for 22 min. The precipitate is taken, washed with deionized water, and dried to obtain a primary composite filler. The boron nitride is spherical nano boron nitride with a particle size of 200nm; The mass concentration of the titanium tetrachloride aqueous solution is 30%; The mass concentration of the aluminum chloride aqueous solution is 10%; The mass concentration of the sodium hydroxide aqueous solution is 10%; 2. Hydrophobicization: Add 200 g of primary composite filler, 22 mL of vinyltrimethoxysilane, and 3100 mL of anhydrous ethanol to a reactor with a reflux device, stir and reflux, control the temperature during stirring and reflux to 50 ° C, the stirring speed to 250 rpm, stir and reflux for 6.5 hours, add to a centrifuge for centrifugation, control the temperature during centrifugation to room temperature, the centrifugal speed to 9500 rpm, centrifuge for 22 minutes, take the precipitate, wash it with anhydrous ethanol and dry it to obtain a composite filler.
[0012] A preparation method of an inorganic floor coating, specifically comprising: weighing raw materials according to specified weight parts, adding a mixed silica sol into a high-speed disperser for high-speed dispersion, controlling the temperature during high-speed dispersion to room temperature, controlling the rotation speed to 5200 rpm, dispersing at high speed for 15 minutes, adding a composite filler, dispersing at high speed for 45 minutes, adding pigment, lithium carbonate, acrylic acid, and tributyl phosphate, stopping stirring and standing for 35 minutes, continuing high-speed dispersion, controlling the temperature during high-speed dispersion to room temperature, controlling the rotation speed to 2800 rpm, dispersing at high speed for 2 hours, and obtaining the inorganic floor coating.
[0013] Example 3 An inorganic floor coating, composed of the following components by weight: 70 parts of mixed silica sol, 15 parts of composite filler, 8 parts of pigment, 4 parts of lithium carbonate, 1.2 parts of acrylic acid, and 0.6 parts of tributyl phosphate; The pigment is chromium oxide; The preparation method of the mixed silica sol is: 1. Coating: 100g hydroxyapatite and 1000mL polyvinyl alcohol aqueous solution were added to a reactor and stirred, the temperature during stirring was controlled to be room temperature, the stirring speed was 300rpm, and the stirring was performed for 1.5h. The mixture was added to a centrifuge and centrifuged, the temperature during centrifugation was controlled to be room temperature, the centrifugal speed was 10000rpm, and the centrifugation was performed for 25min. The precipitate was taken, washed with deionized water and dried, and 1000mL deionized water was added to a reactor and stirred, the temperature during stirring was controlled to be 60°C, the stirring speed was 300rpm, and the stirring was performed for 20min. 400mL glutaraldehyde aqueous solution was added dropwise, the dropping speed was controlled to be 15mL / min, and the stirring was continued for 3h after the dropping was completed. The mixture was added to a centrifuge and centrifuged, the temperature during centrifugation was controlled to be room temperature, the centrifugal speed was 10000rpm, and the centrifugation was performed for 25min. The precipitate was taken, washed with deionized water and dried to obtain coated hydroxyapatite; The particle size of the hydroxyapatite is 200 nm; The polyvinyl alcohol aqueous solution is polyvinyl alcohol 1788 aqueous solution with a mass concentration of 1%; The mass concentration of the glutaraldehyde aqueous solution is 5%; 2. Mixing: Add 5000 mL of silica sol and 15 g of coated hydroxyapatite into a reactor and stir. Control the stirring temperature to be room temperature and the stirring speed to be 300 rpm for 60 min to obtain a mixed silica sol. The pH of the silica sol is 9.5, the particle size is 15 nm, and the mass content of silicon dioxide is 30%; The preparation method of the composite filler is: 1. Compounding: Mix 200g of boron nitride and 2500mL of deionized water, add them to an ultrasonic oscillator for ultrasonic oscillation, control the temperature during ultrasonic oscillation to be room temperature, the frequency to be 30kHz, and the ultrasonic oscillation to be 40min, add them to a reactor for stirring, control the temperature during stirring to be room temperature, the stirring speed to be 300rpm, stir for 20min, add 65mL of titanium tetrachloride aqueous solution, control the dropping speed to be 5mL / min, and after the addition is completed, add 145mL of aluminum chloride aqueous solution, control the dropping speed to be 10mL / min After the addition is completed, 34 mL of sodium hydroxide aqueous solution is added dropwise, and the dropping speed is controlled to be 5 mL / min. After the addition is completed, stirring is continued for 60 min, and the mixture is added to a hydrothermal reactor. The hydrothermal reactor is sealed and then added to an oven for hydrothermal reaction. The temperature during the hydrothermal reaction is controlled to be 180°C. The hydrothermal reaction is carried out for 9 hours. The hydrothermal reactor is taken out and opened, and the mixture is added to a centrifuge for centrifugation. The temperature during the centrifugation is controlled to be room temperature, and the centrifugal speed is 10000 rpm. The mixture is centrifuged for 25 min. The precipitate is taken, washed with deionized water and dried to obtain a primary composite filler. The boron nitride is spherical nano boron nitride with a particle size of 200nm; The mass concentration of the titanium tetrachloride aqueous solution is 30%; The mass concentration of the aluminum chloride aqueous solution is 10%; The mass concentration of the sodium hydroxide aqueous solution is 10%; 2. Hydrophobicization: Add 200 g of primary composite filler, 25 mL of vinyltrimethoxysilane, and 3200 mL of anhydrous ethanol to a reactor with a reflux device, stir and reflux, control the temperature during stirring and reflux to 55 ° C, the stirring speed to 300 rpm, stir and reflux for 7 hours, add to a centrifuge for centrifugation, control the temperature during centrifugation to room temperature, the centrifugal speed to 10000 rpm, centrifuge for 25 minutes, take the precipitate, wash it with anhydrous ethanol and dry it to obtain a composite filler.
[0014] A preparation method of an inorganic floor coating, specifically comprising: weighing raw materials according to specified weight parts, adding a mixed silica sol into a high-speed disperser for high-speed dispersion, controlling the temperature during high-speed dispersion to room temperature, controlling the rotation speed to 5500rpm, dispersing at high speed for 20 minutes, adding a composite filler, dispersing at high speed for 50 minutes, adding pigment, lithium carbonate, acrylic acid, and tributyl phosphate, stopping stirring and standing for 40 minutes, continuing high-speed dispersion, controlling the temperature during high-speed dispersion to room temperature, controlling the rotation speed to 3000rpm, dispersing at high speed for 2 hours, and obtaining the inorganic floor coating.
[0015] Comparative Example 1 On the basis of the composition of the inorganic floor coating of Example 2, an equal mass of silica sol is used instead of the addition of mixed silica sol; The pH value of the silica sol is 9.5, the particle size is 15 nm, and the mass content of silicon dioxide is 30%.
[0016] The rest of the technical solutions are the same as those in Example 2.
[0017] Comparative Example 2 On the basis of the composition of the inorganic floor coating of Example 2, a mixture of boron nitride, titanium dioxide, and aluminum oxide is used in place of the addition of the composite filler; The boron nitride is spherical nano boron nitride with a particle size of 200nm; The particle size of the titanium dioxide is 100 nm; The particle size of the aluminum oxide is 100 nm; The mass ratio of boron nitride, titanium dioxide and aluminum oxide in the mixture of boron nitride, titanium dioxide and aluminum oxide is 200:7.8:5.4.
[0018] The rest of the technical solutions are the same as those in Example 2.
[0019] Performance Test 1 The appearance before drying, the appearance after drying, the volatile organic compound content, the initial fluidity, the abrasion resistance, the surface resistance, the pencil hardness, the surface drying time, the actual drying time, the adhesion grade, the tensile bond strength, the water resistance, and the water contact angle of the inorganic floor coatings prepared in Examples 1-3 and Comparative Examples 1-2 were tested, and the test results are as follows:
[0020] Performance Test 2 The inorganic floor coatings prepared in Examples 1-3 and Comparative Examples 1-2 were sealed and stored at 25° C. for 3 months, and then the appearance before drying was tested. The test results are as follows:
[0021] Performance Test 3 After the inorganic floor coatings prepared in Example 1-3 and Comparative Example 1-2 were dried, they were left to stand at 60°C for 28 days, and then the wear resistance and tensile bond strength were tested. The test results are as follows:
[0022] Performance Test 4 After the inorganic floor coatings prepared in Example 1-3 and Comparative Example 1-2 were dried, they were left to stand at -40°C for 28 days, and then the wear resistance and tensile bond strength were tested. The test results are as follows:
[0023] It can be seen from the results of performance tests 1-4 that the appearance after drying, initial fluidity, abrasion resistance, surface resistance, pencil hardness, surface drying time, actual drying time, adhesion grade, tensile bond strength, water contact angle, storage resistance, high temperature resistance, and low temperature resistance of the inorganic floor coating prepared in Comparative Examples 1-2 are worse than those of the inorganic floor coating prepared in Example 2; The inorganic floor coating prepared in Example 2 is added with mixed silica sol and composite filler, wherein the preparation method of the mixed silica sol includes coating and mixing, wherein the coating is to mix hydroxyapatite with polyvinyl alcohol aqueous solution and then stir, and polyvinyl alcohol is adsorbed on the surface of hydroxyapatite by the adsorption capacity of hydroxyapatite, and then mixed with glutaraldehyde aqueous solution, glutaraldehyde and polyvinyl alcohol are cross-linked, and a layer of cross-linked polyvinyl alcohol is coated on the surface of hydroxyapatite to obtain coated hydroxyapatite, and then the coated hydroxyapatite is mixed with silica sol. The surface of the composite hydroxyapatite contains hydroxyl groups, which can form hydrogen bonds with the silica sol, thereby stabilizing the silica sol, and the hydroxyapatite will release phosphate. The composite filler can promote the cross-linking of silicon dioxide particles during drying; the preparation method of the composite filler includes composite and hydrophobicization, the composite is to coat a layer of porous composite of titanium dioxide and aluminum oxide on the surface of spherical nano boron nitride by a hydrothermal method to obtain a primary composite filler with a spherical shape, thereby avoiding the influence of boron nitride, titanium dioxide and aluminum oxide on the fluidity of the inorganic floor coating when they are added separately, and the hydrophobicization is to use vinyl trimethoxy silane to modify the surface of the primary composite filler, and the vinyl trimethoxy silane reacts with part of the hydroxyl groups on the surface of the primary composite filler to introduce vinyl, thereby improving the hydrophobicity of the primary composite filler, thereby improving the waterproofness of the prepared inorganic floor coating.
[0024] Unless otherwise specified, all percentages used in the present invention are by mass.
[0025] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. An inorganic floor coating, characterized in that: The composition is composed of the following components by weight: 65-70 parts of mixed silica sol, 13-15 parts of composite filler, 7.5-8 parts of pigment, 3.5-4 parts of lithium carbonate, 1-1.2 parts of acrylic acid, and 0.5-0.6 parts of tributyl phosphate; The preparation method of the mixed silica sol comprises the following steps: coating and mixing; The coating comprises mixing hydroxyapatite and polyvinyl alcohol aqueous solution, stirring at room temperature, centrifuging, taking precipitate, washing and drying, mixing with deionized water, stirring at 40-60° C., dropping glutaraldehyde aqueous solution, continuing stirring after the dropping, centrifuging, taking precipitate, washing and drying to obtain coated hydroxyapatite; The mixing comprises mixing the silica sol and the coated hydroxyapatite, and stirring at room temperature to obtain a mixed silica sol; The preparation method of the composite filler comprises the following steps: compounding and hydrophobizing; The composite comprises mixing boron nitride and deionized water, performing ultrasonic oscillation, stirring at room temperature, dropping titanium tetrachloride aqueous solution, dropping aluminum chloride aqueous solution after the dropping, dropping sodium hydroxide aqueous solution after the dropping, continuing stirring after the dropping, hydrothermally reacting at 170-180° C. for 8-9 hours, centrifuging, taking precipitate, washing and drying to obtain primary composite filler; For the hydrophobization, the primary composite filler, vinyl trimethoxysilane and anhydrous ethanol are mixed, stirred and refluxed at 45-55° C., centrifuged, and the precipitate is taken, washed and dried to obtain the composite filler.
2. The inorganic floor coating according to claim 1, characterized in that: In the coating, the dosage ratio of hydroxyapatite, polyvinyl alcohol aqueous solution, deionized water, and glutaraldehyde aqueous solution is 100g:950-1000mL:900-1000mL:350-400mL; The particle size of the hydroxyapatite is 200 nm; The polyvinyl alcohol aqueous solution is polyvinyl alcohol 1788 aqueous solution with a mass concentration of 1%; The mass concentration of the glutaraldehyde aqueous solution is 5%; The dropping speed of the glutaraldehyde aqueous solution is 10-15 mL / min.
3. The inorganic floor coating according to claim 1, characterized in that: In the mixing, the ratio of silica sol to coated hydroxyapatite is 5000mL:14-15g; The pH value of the silica sol is 9.5, the particle size is 15 nm, and the mass content of silicon dioxide is 30%.
4. The inorganic floor coating according to claim 1, characterized in that: In the composite, the dosage ratio of boron nitride, deionized water, titanium tetrachloride aqueous solution, aluminum chloride aqueous solution and sodium hydroxide aqueous solution is 200g:2000-2500mL:60-65mL:135-145mL:30-34mL.
5. The inorganic floor coating according to claim 1, characterized in that: In the composite, the boron nitride is spherical nano boron nitride with a particle size of 200 nm; The mass concentration of the titanium tetrachloride aqueous solution is 30%; The mass concentration of the aluminum chloride aqueous solution is 10%; The mass concentration of the sodium hydroxide aqueous solution is 10%; The dropping speed of the titanium tetrachloride aqueous solution is 4-5 mL / min; The dropping speed of the aluminum chloride aqueous solution is 8-10 mL / min; The dropping speed of the sodium hydroxide aqueous solution is 4-5 mL / min; The temperature of the ultrasonic oscillation is room temperature, the frequency is 25-30 kHz, and the time is 30-40 minutes.
6. The inorganic floor coating according to claim 1, characterized in that: In the hydrophobization, the usage ratio of the primary composite filler, vinyltrimethoxysilane and anhydrous ethanol is 200g:20-25mL:3000-3200mL; The pigment is one of iron oxide or chromium oxide.
7. A method for preparing the inorganic floor coating according to any one of claims 1 to 6, characterized in that: After weighing the raw materials according to the specified weight proportions, add the mixed silica sol into a high-speed disperser for high-speed dispersion, control the temperature during high-speed dispersion to room temperature, control the rotation speed to 5000-5500rpm, and disperse at high speed for 10-20min. Add composite fillers and disperse at high speed for 40-50min. Add pigments, lithium carbonate, acrylic acid, and tributyl phosphate, stop stirring and let stand for 30-40min, continue to disperse at high speed, control the temperature during high-speed dispersion to room temperature, control the rotation speed to 2700-3000rpm, and disperse at high speed for 1.5-2h to obtain an inorganic floor coating.
Citation Information
Patent Citations
Preparation method of polyvinyl alcohol / hydroxyapatite (PVA / HA) composite microspheres
CN107376795A
Water-resistant aqueous inorganic zinc-enriched coating with added lithium carbonate hardening agent
CN108285661A
Aqueous environmentally friendly anticorrosion paint for metals and preparation method thereof
CN108929581A
Preparation method of high-thermal-conductivity filler for thermally conductive polymer material
CN110819018A